2019
DOI: 10.18203/2320-1770.ijrcog20191177
|View full text |Cite
|
Sign up to set email alerts
|

The women knowledge, attitude, and perceptions of pre-eclampsia and eclampsia in Madagascar

Abstract: Background: Preeclampsia is a complication of pregnancy responsible for high rates of morbidity and mortality, particularly in Africa and Madagascar. The objective of present study was to assess patients' knowledge, attitudes and beliefs about pre-eclampsia in Madagascar.Methods: This is an observational study on the knowledge, belief and attitudes of women seen at the Befelatanana Gynecology and Obstetrics Hospital and conducted by questionnaires from 1 December 2017 to 30 May 2018.Results: During the study p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…15 The lack of quality and quantity of antenatal consultation is a reason for only 30% of mothers being informed about preeclampsia. 16 According to the maternal age, neither the statistical analysis nor the percentage tendencies showed difference in preeclampsia knowledge. However, based on the educational background, a pattern was seen that the higher the level of education, the more mothers had good knowledge.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…15 The lack of quality and quantity of antenatal consultation is a reason for only 30% of mothers being informed about preeclampsia. 16 According to the maternal age, neither the statistical analysis nor the percentage tendencies showed difference in preeclampsia knowledge. However, based on the educational background, a pattern was seen that the higher the level of education, the more mothers had good knowledge.…”
Section: Resultsmentioning
confidence: 94%
“…This result was also reported in another study, which found serious symptoms including epigastric pain and blurred vision were not recognized by patients. 16 This finding may explain why all of the preeclampsia cases were found to be advanced. 16 Most pregnant women are suffering the main preeclampsia symptoms but they do not realize the actual condition and do not seek health care immediately.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation